ANTIOXIDANT PROPERTIES OF LACTOBACILLUS AND ITS PROTECTING EFFECTS TO OXIDATIVE STRESS CACO-2 CELLS - Dachang Wu; Ming Zhong Sun; Cuili Zhang; Yi Xin (Journal of Animal and Plant Sciences, 2014)
This study was designed to analyse the antioxidant capacity of lactic acid bacteria (LAB) in order to provide characteristic parameters and theoretical basis for its further utilization as a natural antioxidant. Further experiment was carried out to study its protection mechanism through oxidative stress Caco-2 cell model in vitro. For this purpose, antioxidative activity of cells and different cellular fractions of Lactobacillus delbrueckii (ATCC7830) was evaluated by scavenging capacity of superoxide anion free radicals (SAFR)，reducing power and total antioxidant capacity assay. Low dose of H2O2 (100μmol/L) was used to establish oxidative damaged model on Caco-2 cells, the bacteria’s protecting effect on the damaged cells was further researched. The results showed that extracellular secretions of Lactobacillus delbrueckii has the strongest antioxidant activity, following by cells, and cells can clear superoxide radicals. The ability to scavenge SAFR of this LAB was (42.4±0.32) % (cell lysates, the highest), the reducing power was (3.01±0.20, cell extracellular secretions, the highest), and the total antioxidant ability was (4.32±0.36, cell extracellular secretions, the highest). The above antioxidative character made this LAB possible to protect Caco-2 cells being damaged by low dose of H2O2. Further analysis showed that the total antioxidant capacity (T-AOC) of culture supernatant and lysate were significantly increased compared with the negative control group and the oxidative stress group (p<0.01). Also increased the anti-superoxide anion (O2-) free radicals (p<0.01) level. All the results indicate that different fractions from lactic acid bacteria have various capabilities on reducing power, scavenging superoxide anion free radicals ability and total antioxidant capacity. Extracellular secretions have the most obvious antioxidant character. Lactobacillus delbrueckii could protect Caco-2 cells under oxidative stress by increasing its antioxidative function in vitro.
Keywords: Antioxdiative; Lactobacillus; oxidative stress; Caco-2 cell; in vitro